PEMANFAATAN DIGITAL LIBRARY PADA PERPUSTAKAAN KAMPUNG PENDIDIKAN DESA KUAJANG KABUPATEN POLEWALI MANDAR - Safriansyah; Nur Hafsah Yunus MS; Arifin TAHIR; Syarli; Wahyuddin (Pusat Pengabdian kepada Masyarakat- LPPM Universitas Terbuka, 2020)
The lack of interest in reading nowadays is one of the factors in the decline of the nation's regeneration that loves literacy. The Education Village Library Group of Kuajang Village, Binuang District is one of the literacy movements established in Kuajang Village. This library is part of a project of teenagers and hamlet residents to build a literacy village to feel the equal distribution of education without having to abandon the value of local wisdom. In addition, it also aims to increase public interest in reading through the development of an appropriate technology as a solution, namely the digital library. The method of implementation is in accordance with the planning stages that have been prepared, namely the stages of activities that begin with the coordination and analysis of needs (Phase I), digital library application design (Phase II), application integration in the framework model (Phase III), and the use of systems in the field (Stage IV). The results show that the application development uses the OPAC (Online Public Access Catalog) model that can facilitate the user in the process of searching for books and the initial display of the digital library system in the form of a catalog. To optimize the use and utilization of this application, training is carried out to users and managers of the Education Village Library Group. In addition, periodic monitoring and assistance will be carried out to ensure the use of this system can be operated and the benefits are felt by the community